1998
DOI: 10.1055/s-0037-1615379
|View full text |Cite
|
Sign up to set email alerts
|

Deletion Polymorphism in the Angiotensin-converting Enzyme Gene as a Thrombophilic Risk Factor after Hip Arthroplasty

Abstract: SummaryDespite thromboprophylaxis, deep vein thrombosis is a common complication of major orthopedic surgery. Predisposing genetic risk factors are unknown. In this case-control study, we investigated the association of the insertion (I)/deletion (D) angiotensin converting enzyme (ACE) gene polymorphism, Factor V Leiden (R506Q) mutation, and 5,10 methylenetetrahydrofolate reductase (MTHFR) gene polymorphism with post-operative venous thrombosis in 85 patients who underwent elective total hip arthroplasty. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…A recent meta-analysis including 39 case–control studies showed that ACE I/D polymorphism was significantly associated with intracranial hemorrhage, especially among Asians [ 13 ]. Although some studies have described the DD genotype as a potent thrombophilic factor [ 26 , 27 ], several studies have reported that D allele carriers of ACE have increased risk of hemorrhagic stroke [ 28 ] and blood loss after hip surgery [ 29 ], which is also consistent with our results.…”
Section: Discussionsupporting
confidence: 92%
“…A recent meta-analysis including 39 case–control studies showed that ACE I/D polymorphism was significantly associated with intracranial hemorrhage, especially among Asians [ 13 ]. Although some studies have described the DD genotype as a potent thrombophilic factor [ 26 , 27 ], several studies have reported that D allele carriers of ACE have increased risk of hemorrhagic stroke [ 28 ] and blood loss after hip surgery [ 29 ], which is also consistent with our results.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have reported a correlation between ACE polymorphisms and susceptibility to acute respiratory distress syndrome (ARDS) [8]. The deletion allele (D), defined as a D/D genotype, results in elevated expression and activity of ACE [9], mediating ARDS and mortality risk [8], increased obesity [10], thrombophilia [11], hypertension [12], and cardiovascular diseases [13]. Interestingly, the development of high blood pressure and cardiovascular disorders are common comorbidities in patients infected with SARS-CoV-2, and correlate with susceptibility to hospitalization and mortality [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…It could be more sensibly justi ed since the spread, pathogenicity and mortality of SARS-CoV-2 can be attributed to several predisposing factors in population (Singhal 2020). Furthermore, the genetic variants of ACE have been already con rmed to be associated with the prognosis of some non-infectious lung diseases such as asthma (Gao et (Philipp et al 1998), as well as increased mortality in acute respiratory distress syndrome (ARDS) (Marshall et al 2002). Recent ndings have shown that all these clinical conditions are related to more aggressive type of COVID-19 (Wiersinga et al 2020).…”
Section: Introductionmentioning
confidence: 99%